2019
DOI: 10.1002/ddr.21596
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin ameliorates preeclampsia phenotypes by inhibiting TFPI‐2 and HIF‐1α/VEGF in a l‐NAME induced rat model

Abstract: Preeclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality with few safe, effective, and minimally invasive therapeutics. Inflammation, oxidative stress, and angiogenic imbalance have been reported to contribute to PE pathogenesis. Vitexin (VI) possesses various pharmacological activities including the potent regulation of the above biological processes in different conditions. This study aims to investigate whether VI has therapeutic potential to PE and the underlying mechanisms. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Physiologic and histologic perturbations induced by gestational L-NAME largely resemble clinical manifestations of PE. This includes 1) elevated placental expression of inflammatory, antiangiogenic, and apoptotic factors; 2) reduced antioxidant activity; and 3) increased glomerular area, capillary structure disorder, abnormal protein cast, and reduced nephron numbers (Amaral et al, 2018;Shu et al, 2018;Chen et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologic and histologic perturbations induced by gestational L-NAME largely resemble clinical manifestations of PE. This includes 1) elevated placental expression of inflammatory, antiangiogenic, and apoptotic factors; 2) reduced antioxidant activity; and 3) increased glomerular area, capillary structure disorder, abnormal protein cast, and reduced nephron numbers (Amaral et al, 2018;Shu et al, 2018;Chen et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that the levels of mRNA and protein expression of placental HIF1A were significantly increased in rats administered 0.5 mg/ml of L-NAME via drinking water from GD 6 to GD 10. Also, in another study, dramatically increased placental HIF1 protein level is observed in KO mice with a deficiency in COMT (28,29). However, in our study, hypoxia increased the levels of HIF1A, while L-NAME and COMT-I did not.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, vitexin decreased the expression levels of sFlt and PlGF, which play key roles in the pathogenesis of preeclampsia. Also, vitexin at a dose of 60 mg/kg was more effective in low pups/placenta ratio [86]. All results have been summarized in Table 1.…”
Section: Plant Phenolic Compounds In Animal Models Of Preeclampsiamentioning
confidence: 91%
“…Vitexin shows a wide range of pharmacological activities, such as anti-hypertensive and anti-inflammatory effects and protective properties in the cardiovascular system [48,85]. Interesting results were obtained by Zheng et al [86] in an animal model of preeclampsia.…”
Section: Vitexinmentioning
confidence: 99%
See 1 more Smart Citation